Catecholamine-induced transport systems in trout erythrocyte. Na+/H+ countertransport or NaCl cotransport? (The Rockefeller University Press, 1986)
It has previously been shown (Baroin, A., F. Garcia-Romeu, T. Lamarre, and R. Motais. 1984a, b. Journal of Physiology. 350:137, 356:21; Mahe, Y., F. Garcia-Romeu, and R. Motais. 1985. European Journal of Pharmacology. 116:199) that the addition of catecholamines to an isotonic suspension of nucleated red blood cells of the rainbow trout first stimulates a cAMP-dependent, amiloride-sensitive Na+/H+ exchange. This stimulation seems to be transient. It is followed by a more permanent activation of a coupled entry of Na+ and Cl-, which is inhibited by amiloride but also by inhibitors of band 3 protein (DIDS, furosemide, niflumic acid). The coupled entry of Na+ and Cl- could therefore result from the parallel and simultaneous exchange of Na+out for H+in (via the cAMP-dependent Na+/H+ antiporter) and Cl- out for HCO3- in (via the anion exchange system located in band 3 protein). However, in view of the following arguments, it had been proposed that NaCl uptake does not proceed by the double-exchanger system but via an NaCl cotransport: (a) Na+ entry requires Cl- as anion (in NO3- medium, the Na uptake is strongly inhibited, whereas NO3- is an extremely effective substitute for Cl- in the anion exchange system); (b) Na uptake is not significantly affected by the presence of HCO3- in the suspension medium despite the fact that in red cells, Cl-/HCO3- exchange occurs more readily than the exchanges of Cl- for basic equivalents in a theoretically CO2-free medium (the so-called Cl-/OH- exchanges). The purpose of the present paper was a reassessment of the two models by using monensin, an ionophore allowing Na+/H+ exchange. From this study, it appears that NaCl entry results from the simultaneous functioning of the Na+/H+ antiporter and the anion exchange system. The apparent Cl dependence is explained by the fact that, in these erythrocytes, NO3- clearly inhibits the turnover rate of the Na+/H+ antiporter. As Na+/H+ exchange is the driving component in the salt uptake process, this inhibition explains the Cl requirement for Na entry. The lack of stimulation of cell swelling by bicarbonate is explained by the fact that the rate of anion exchange in a CO2-free medium (Cl-/OH- exchange) is roughly equivalent to that of Na+/H+ exchange and thus in practice is not limiting to the net influx of NaCl through the two exchangers.(ABSTRACT TRUNCATED AT 400 WORDS)